2022
DOI: 10.3390/ijms23147941
|View full text |Cite
|
Sign up to set email alerts
|

Targeted-Deletion of a Tiny Sequence via Prime Editing to Restore SMN Expression

Abstract: Spinal muscular atrophy (SMA) is a devastating autosomal recessive motor neuron disease associated with mutations in the survival motor neuron 1 (SMN1) gene, the leading genetic cause of infant mortality. A nearly identical copy gene (SMN2) is retained in almost all patients with SMA. However, SMN2 fails to prevent disease development because of its alternative splicing, leading to a lack of exon 7 in the majority of SMN2 transcripts and yielding an unstable truncated protein. Several splicing regulatory eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…To explore the enhancer effect of C400 and its application for universal targeted gene therapy for HA in different genetic backgrounds, we nucleofected F8 expression vectors into the rDNA loci of HA-iPSCs and normal human iPSCs (B6-iPSCs), respectively. Both iPSCs were previously established [26,27]. After selection using G418, single clones were selected for identification.…”
Section: Rdna-specific Integration Of the Novel F8 Cassette Into Ipsc...mentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the enhancer effect of C400 and its application for universal targeted gene therapy for HA in different genetic backgrounds, we nucleofected F8 expression vectors into the rDNA loci of HA-iPSCs and normal human iPSCs (B6-iPSCs), respectively. Both iPSCs were previously established [26,27]. After selection using G418, single clones were selected for identification.…”
Section: Rdna-specific Integration Of the Novel F8 Cassette Into Ipsc...mentioning
confidence: 99%
“…(1) Cell lines were purchased from Procell Life Science & Technology (Wuhan, China) and cultured in DMEM/HG (Gibco, Grand Island, NY, USA) supplemented with 10% fetal bovine serum (FBS; Gibco) and split every 3-4 days. (2) iPSCs, HA-iPSCs [26], and B6-iPSCs (also referred to as hiPSCs) [27] have been generated. All iPSCs were cultured on Matrigel (BD Biosciences, Franklin Lakes, NJ, USA) -coated well plates (Corning, NY, USA) in mTesR plus medium (StemCell Technologies, Vancouver, BC, Canada).…”
Section: Cell Culturementioning
confidence: 99%
“…Its editing flexibility and ability to correct indels and introduce large deletions, which base editing cannot achieve, make it a highly effective method. Although relatively new to the cardiac research field, prime editing has already demonstrated efficiency in generating cell and animal models of DMD ( Zhou et al, 2022c ; Happi Mbakam et al, 2022a ,b; Chemello et al, 2021 ), which could eventually help identify new drug targets or potential therapies for cardiac disease. Compared to other gene editing technologies, PE has the advantage of reduced off-target effects, making it a highly desirable therapeutic option.…”
Section: Prime Editing’s Potential In Cardiac Researchmentioning
confidence: 99%
“…Most patients with SMA are characterized by exon 7 skipping in the SMN2 transcript, producing unstable truncated proteins. Zhou et al ( 93 ) inser-ted full-length SMN into SMA patient-derived iPSCs by inducing a targeted 9bp-deletion in the intronic splicing silencer-N1 of SMN2 with a prime editor. In the motor neurons derived from rescued iPSCs, apoptosis was reduced by restoring SMN protein.…”
Section: Stem Cell Research Applied With the Crispr Systemmentioning
confidence: 99%